2004
DOI: 10.1099/mic.0.26825-0
|View full text |Cite|
|
Sign up to set email alerts
|

Are some putative glycogen accumulating organisms (GAO) in anaerobic : aerobic activated sludge systems members of the α-Proteobacteria?

Abstract: Activated sludge plants designed to remove phosphorus microbiologically often perform unreliably. One suggestion is that the polyphosphate-accumulating organisms (PAO) are out-competed for substrates by another group of bacteria, the glycogen-accumulating organisms (GAO) in the anaerobic zones of these processes. This study used fluorescence in situ hybridization (FISH) and denaturing gradient gel electrophoresis (DGGE) to analyse the communities from laboratory-scale anaerobic : aerobic sequencing batch react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 41 publications
2
43
0
1
Order By: Relevance
“…DF2MIX (Table 1) Defluvicoccus-related organisms accounted for an additional 8 % (SEM=1 %) of the Bacteria, and the cells that bound these probes were TFOs. The fact that the majority of Alphaproteobacteria in the biomass that cycled PHA did not bind the current probes for GAOs strongly suggests the presence of other GAOs, despite the similar morphology of these organisms to those described in the literature (Beer et al, 2004;Meyer et al, 2006;Wong et al, 2004). It may be that the probes from these publications do not target the diversity of the organisms within these already identified groups so that additional sequences are required in order to broaden the probe specificities; alternatively, another group of GAOs unrelated to Sphingomonas or D. vanus may exist.…”
Section: Fish and Post-fish Chemical Stainingmentioning
confidence: 65%
See 1 more Smart Citation
“…DF2MIX (Table 1) Defluvicoccus-related organisms accounted for an additional 8 % (SEM=1 %) of the Bacteria, and the cells that bound these probes were TFOs. The fact that the majority of Alphaproteobacteria in the biomass that cycled PHA did not bind the current probes for GAOs strongly suggests the presence of other GAOs, despite the similar morphology of these organisms to those described in the literature (Beer et al, 2004;Meyer et al, 2006;Wong et al, 2004). It may be that the probes from these publications do not target the diversity of the organisms within these already identified groups so that additional sequences are required in order to broaden the probe specificities; alternatively, another group of GAOs unrelated to Sphingomonas or D. vanus may exist.…”
Section: Fish and Post-fish Chemical Stainingmentioning
confidence: 65%
“…One group are members of the order Sphingomonadales, and the other is related to the isolate Defluvicoccus vanus within the order Rhodospirillales. Both of these organisms could consume acetate as the sole carbon source (Beer et al, 2004;Wong et al, 2004), but the D. vanus-related organism has also been recently demonstrated to consume propionate (Meyer et al, 2006), unlike Competibacter.…”
Section: Introductionmentioning
confidence: 99%
“…FISH showed that Actinobacteria, mainly consisting of two probe-defined actinobacterial PAO groups, constituted 13 % of the bacterial biovolume, while no actinobacterial clone was retrieved in the clone library analysis. This could be due to the difficulty of extracting DNA from Gram-positive bacteria (Beer et al, 2004), PCR bias and/or low cloning number (Head et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…(Meyer et al, 2006), SBR9-1a for Alphaproteobacteria Sphingomonas spp. (Beer et al, 2004), PAOMIX (Crocetti et al, 2000) for the Betaproteobacteria Accumulibacter spp., and GAOMIX (equal amounts of GAOQ989 and GB_G2 Kong et al, 2002) for the Gammaproteobacteria Competibacter spp. All microscopic examinations were carried out using a Zeiss LSM510 Meta confocal laser scanning microscope (CLSM).…”
Section: Methodsmentioning
confidence: 99%
“…These organisms have been phylogenetically identified as closely related to the pure culture Defluviicoccus vanus (Meyer et al, 2006;Wong et al, 2004) and Sphingomonas spp. (Beer et al, 2004). Due to the nature of the lab-scale studies carried out by enrichment of microorganisms on sole organic carbon substrates, key aspects of their ecophysiology in full-scale plants are not known.…”
Section: Introductionmentioning
confidence: 99%